Drugs in sport — testing results from the South African Laboratory 1995 - 2002 - Van der Merwe, PJ (South African journal of sports medicine, 2004)
Objective. To summarise the results of the past 8 years obtained at the South African Doping Control Laboratory and to compare the results with international statistics. Method. Screening procedures were performed on 14 017 urine samples collected from competitors in 54 different sporting codes during the period 1995 - 2002. Samples were analysed using gas chromatography and gas chromatography/mass spectrometry for the presence of prohibited substances, which are listed by the International Olympic Committee (IOC). Results. The results obtained were compared with those of the IOC-accredited laboratories. Prohibited substances were detected in 300 samples (2.14%), of which 45.6% contained anabolic agents and 34.6% stimulants. The positive samples from the IOC laboratories contained 58.7% anabolic agents and 20.8% stimulants. Testosterone and nandrolone were the anabolic agents most frequently detected in positive samples, both in South Africa and internationally. The ephedrines as a group accounted for most stimulants detected in positive samples. Conclusion. It is of concern that the percentage of positive samples (2.14%) obtained in our laboratory is higher than the 1.70% in IOC laboratories. It is therefore necessary that doping control to curb the use of prohibited substances should continue and expand. South African Journal of Sports Medicine Vol.16(1) 2004: 29-32